Pengaruh Transformasi Digital Dan Gaya Kepemimpinan Terhadap Kinerja Karyawan Dengan Komitmen Organisasi Sebagai Variabel Intervening Pada Dinas Peternakan Dan Kesehatan Hewan Sumatera Barat - Serly Novia Putri; Vicky Brama Kumbara; Andre Ilyas (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to analyze the effect of digital transformation and leadership style on employee performance with organizational commitment as an intervening variable at the Department of Animal Husbandry and Animal Health of West Sumatra Province. The study applies a quantitative approach using a survey method. Data were collected through questionnaires distributed to employees and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS software. The independent variables are digital transformation and leadership style, the dependent variable is employee performance, and the intervening variable is organizational commitment. The results show that digital transformation has a positive and significant effect on organizational commitment and employee performance. Leadership style has a negative and insignificant effect on organizational commitment and employee performance. Organizational commitment has a negative and insignificant effect on employee performance. Indirect testing indicates that digital transformation and leadership style do not have a significant effect on employee performance through organizational commitment, and organizational commitment does not mediate the relationship between leadership style and employee performance. These findings indicate that strengthening digital transformation implementation is a key factor in improving employee performance in public sector institutions.